Rethinking the policy objectives of development aid: From economic growth to conflict prevention - Sakiko Fukuda-Parr (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The current consensus objective of development aid in the international community is to reduce poverty in general and to achieve the Millennium Development Goals (MDGs) in particular. In addition, the dominant view identifies economic growth as the principal means to this end. But the policy objective of aid can be defined in many ways, and has in fact varied over time with shifting priorities within the international community about the ultimate ends of development and the means for advancing those ends. This paper argues that more attention should be given to conflict prevention as a policy objective of development aid and explores the implications of doing so for aid programme priorities and the international aid architecture in general. The paper shows that violent conflict is a major obstacle to achieving the MDGs; it identifies 64 worst performing countries and finds that the majority have experienced violent internal conflict, and/or are vulnerable because of the socioeconomic correlates of internal war. The paper then argues that development policy priorities and their support with aid can be deployed to reduce these risks. Conflict prevention is thus an important policy objective as a means to achieving MDGs as well as an end itself since security from violence is an essential aspect of human wellbeing and human security. Integrating this policy objective would imply adjustments that would need to be made in aid architecture.
Keywords: F35; F53; I38; 330; aid; fragile states; conflict; human security; poverty; human development; donor policies; Entwicklungshilfe; Millennium Development Goals